PERCULARITIES OF ORGANIZATION OF LEARNING PROCESS IN THE CONTEXT OF STEAM EDUCATION TECHNOLOGY - Xo’jamiyorov, Islom (Журнал математики и информатики, 2021)
In this research work about the problems of the learning process mathematics for students in the STEAM education is investigated. The STEAM technology of education allows creating in schoolchildren skills in conducting a laboratory experiment, understanding of fundamental scientific concepts and laws, ability to apply modern tools of activity, critical thinking and creativity.